Da’wah Ecology in Digital Space: A Study of Tiktok Content Pandawara Group Account - Aqillah, Muyassyifa Ayu; Wahyuningsih, Sri; Aninnas, Afina (TATHO: International Journal of Islamic Thought and Sciences, 2024)
Ecological problems are an important concern for all religious communities. For Muslims, to overcome this problem can be through the dissemination of Islamic da’wah values in the community. This qualitative study with content analysis aims to analyze the message of da’wah in the Tiktok content of Pandawara Group's actions and what impact it has on society. The results of the study found that there are dimensions of theological and ecological orientation in da’wah messages from the content of the Pandawaragroup tiktok account. Meanwhile, the social implications of the content can strengthen public concern for the conservation of the natural environment. This study confirms that the TikTok application can be an effective medium in disseminating Islamic da’wah values that are related to strengthening theological and ecological aspects to the community.